Ion Implantation Damage in Quartz - Macaulay-Newcombe, George Richard (My University, 1991)
This thesis is a report on a series of measurements of ion-bombardment effects on α-quartz crystals. Damage was produced in α-quartz (single-crystal SiO₂) by bombarding with ions of ⁴He⁺ to ²⁰⁹Bi⁺⁺ in the energy range of 15 - 200 keV, at both 300 K and ≤ 50 K. The samples were analysed in - situ with Rutherford backscattering/channeling, using 1 - 2 MeV ⁴He⁺ ions; data was obtained from both the oxygen and silicon peaks, so that damage stoichiometry could be calculated. At low ion fluences (~ 10¹⁰ - 10¹¹ ions/mm²) the apparent damage level increases linearly with fluence, but at rates of about 3 - 19 times greater than predicted by the modified Kinchin-Pease equation. At higher fluences (~ 10¹¹ - 10¹² ions/mm²) the rate of damage increases with fluence for elastic energy deposition rates of less than :::= 0.08 eV/atom, but remains constant for greater elastic energy deposition rates. At even higher ion fiuences saturation of the damage occurs. It has been observed that the analysis beam creates damage at a rate dependent on the level of damage already present in the crystal; furthermore, the damage created by the analysis ions appears to be predominantly due to the inelastically deposited energy. Strain effects seem to greatly exaggerate the level of damage indicated by simple channeling calculations. A simple model is proposed to explain both the high rates of damage production and the non-stoichiometry of the damage. The model indicates that the effects of elastic energy deposition, inelastic energy deposition, strain produced by damage, and lattice relaxation into a '"quasi-amorphous" state. all contribute to the apparent damage levels synergistically.
Keywords: Materials Science and Engineering; Materials Science and Engineering